Treatment of Recurrent Clostridioides difficile Infection Using Fecal Microbiota Transplantation in Iranian Patients with Underlying Inflammatory Bowel Disease - Azimirad M; Yadegar A; Gholami F; Shahrokh S; Asadzadeh Aghdaei H; Ianiro G; Suzuki H; Cammarota G; Zali MR (Dove Medical Press, 2020)
Masoumeh Azimirad,1 Abbas Yadegar,1 Fatemeh Gholami,1 Shabnam Shahrokh,2 Hamid Asadzadeh Aghdaei,3 Gianluca Ianiro,4 Hidekazu Suzuki,5 Giovanni Cammarota,4 Mohammad Reza Zali2 1Foodborne and Waterborne Diseases Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Gastroenterology and Liver Diseases Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Basic and Molecular Epidemiology of Gastrointestinal Disorders Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Digestive Disease Center, Fondazione Policlinico Universitario Agostino Gemelli IRCCS, Catholic University of Sacred Heart, Rome, Italy; 5Division of Gastroenterology and Hepatology, Department of Internal Medicine, Tokai University School of Medicine, Isehara, Kanagawa 259-1193, JapanCorrespondence: Abbas YadegarFoodborne and Waterborne Diseases Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Shahid Arabi Ave., Yemen St., Velenjak, Tehran, IranEmail a.yadegar@sbmu.ac.irPurpose: Fecal microbiota transplantation (FMT) is an effective treatment option for patients with recurrent Clostridioides difficile infection (rCDI). However, there is a paucity of evidence regarding its efficacy and safety in patients with rCDI and concurrent inflammatory bowel disease (IBD). Here, we present a single-center experience of FMT for treatment of rCDI in Iranian patients with IBD.Patients and Methods: Eight patients with established IBD (7 with ulcerative colitis and 1 with Crohn’s disease) who underwent at least one FMT via colonoscopy for treatment of rCDI were enrolled in this study. Demographics, pre-FMT and post-FMT IBD activity, efficacy for rCDI and adverse events (AEs) were assessed during a 6-month follow-up period. All patients had experienced 3 episodes of rCDI and were refractory to conventional therapies with metronidazole and vancomycin. Primary cure and secondary cure rates were assessed after FMT treatments.Results: A total of 10 FMTs were performed via colonoscopy in 8 patients (6/8; 75% men) with a median age of 35 years (range: 22– 60). Two patients received a second FMT. Overall, the primary and secondary cure rates were 75% and 100%, respectively. Two patients developed CPE-producing C. perfringens diagnoses after second FMTs. There were no other AEs, and no patient experienced IBD flare.Conclusion: We demonstrated that FMT appears to be an effective, safe and rational therapeutic alternative for resolution of rCDI in patients with underlying IBD. Furthermore, we suggest implementing the CPE-producing C. perfringens testing in the screening of FMT donors.Keywords: fecal microbiota transplantation, recurrent Clostridioides difficile infection, inflammatory bowel disease, FMT, rCDI, IBD, Iran